Breathing Life Sustainably - An Abandoned Settlement to an Open-Air Museum Twah Longwar - Naphibahun Lyngdoh (EXARC Journal)
Twah Longwar is an abandoned settlement located in the State of Meghalaya in North-East India. It is located enroute to one of the world's rainiest places on earth – Mawsynram. Twah Longwar is an abandoned settlement with remnants of over twenty old houses, an ancient market, and a burial site. In a place where rainfall is a concern but also a major tourist attraction, and where lost architectural styles are only documented in photographs and oral traditions, an archaeological open-air museum built from traditional 'earth friendly' materials will contribute immensely to showcasing the region's life-sized cultural history. This article will explain how a drone, LiDAR, GIS-based technologies and archaeological methodologies are used to create a digital reproduction of the settlement which is made available to everyone. This will allow those who are unable to travel to learn about Twah longwar's long-lost traditions. The procedure for physically reconstructing the settlement will also be demonstrated. The focus is also to take the museum outside the four walls of a building where generations to come will physically envision the legacy of indigenous architecture and social life, at the same time as safeguarding the environment in and around the site.